Green Extraction of Eurycomanone from Eurycoma longifolia Using Imidazolium-Based Ionic Liquids Combined with Microwave-Assisted Method - Puspita, Esmeralda Dwi; Iswahyudi, Iswahyudi; Ayu, Welinda Dyah; Ahmad, Islamudin (Journal of Pharmaceuticals and Natural Sciences, 2025)
Background: Pasak Bumi (Eurycoma longifolia Jack) is an endemic plant that has been utilized as a medicinal agent by communities in Kalimantan and Sumatra for an extended period. The entirety of E. longifolia, inclusive of its leaves, stems, and roots, has been utilized as a medicinal agent. The primary compound present in E. longifolia is eurycomanone, which is commonly found in the roots of the plant. Objective: This study aims to optimize the extraction of eurycomanone from E. longifolia roots using imidazolium-based ionic liquids (1-butyl-3-methylimidazolium chloride [BMIM][Cl]) through microwave-assisted extraction (MAE), applying response surface methodology (RSM) for statistical meodeling. Methods: A Box-Behnken design was employed to evaluate the effects of three independent variable including [BMIM][Cl]concentration, extraction time, and solid-liquid ratio on eurycomanone content. Quantification was performed using a validated HPLC method, and model performance was assessed via analysis of variance (ANOVA). Results: The concentration of [BMIM][Cl] significantly influenced eurycomanone content (p<0.001), while extraction time and solid-liquid ratio showed no significant individual effects. The optimized condition yielded 0.4061 µg/mg of eurycomanone, closely matching the predicted value (0.3835 µg/mg). The model demonestreated good fit (R2 = 0.8135) and non-significant Lack of Fit (p = 0.6566), indicating reliable predictive capability. Conclusion: MAE using [BMIM][Cl] is an effective and environmentally friendly approach for extracting eurycomanone. The developed model provides a robust framework for process optimization and potential scale-up in phytopharmaceutical applications.